Sequential arrays - Nester, Marks R. (Utilitas Mathematica, 1997)
Those latin squares which are also sequential arrays are classified. The transformation si → sc+ik on the elements of a sequence is briefly studied. If this transformation is applied to an n-ary sequence then the new sequence may not be necklace equivalent to the original sequence. In any case, there is an isomorphism between the sets of sequential arrays associated with these two sequences. The effects of applying this transformation to the labels of a sequential array are also investigated.